Performance Evaluation of Routing Protocols in Wireless Mobile Ad Hoc Networks (MANETS) using OPNET Simulator - Roshanasan, Mohammadamin (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2012)
ABSTRACT: Mobile ad hoc networks (MANETs) have already opened a new point of view in the field of wireless networks which includes hundreds and thousands of nodes. The wireless nodes are communicating without the need of any kind of neither infrastructure like the base stations or routers, nor centralized administration. Wireless nodes are free of moving anytime, anywhere. Therefore, mobile ad hoc networks need to have dynamic routing protocols. Mobile Ad hoc network routing protocols are divided into several different categories such as Proactive, Reactive and Hybrid Routing Protocols. Also there are a lot of performance metrics to compare the routing protocols. Each of them has its own attributes and well for specific area, such as: throughput, jitter, packet delivery ratio, average number of hops, route discovery time and end-to-end delay, which are some important ones. In this thesis three well known routing protocols; Optimized Link State Routing (OLSR), Ad-hoc On-demand Distance Vector (AODV) and Temporary Ordered Routing Algorithm (TORA) were evaluated using the OPNET simulator under the medium load traffic size in FTP protocol. The first one (OLSR) is a proactive protocol depending on routing tables which are maintained at each node. The second one (AODV) is a reactive protocol, that finds a route to a destination on-demand. And the third ones‘ TORA which works in both categories as reactive and proactive. The random waypoint mobility model is used as pattern of mobility. As performance metrics average throughput, average network load and average end-to-end delay are examined in different number of nodes, file sizes and node speeds. The result from the simulations of this study reveals that different protocols have different qualities; some of the protocols perform better than others in one metric when using them in a specific scenario and worse in other metrics. After analyzing performances of some well-known reactive and proactive routing protocols, in case of average throughput, average end-to-end delay and average network load, the superiority of proactive protocols, over reactive ones is observed in different network scenarios. From the simulation results it is observed that the average end-to-end delay increases slightly when the number of nodes increases in OLSR. Also average throughput shown in OLSR was the highest comparing to AODV and TORA. Among the reactive protocols, AODV performs better than TORA when file sizes, speed of nodes and number of nodes are changed. On the other hand, TORA gives a highest end-to-end delay and lowest throughput compared to AODV and OLSR. Keywords: Mobile wireless ad hoc networks, simulation, routing protocols, performance evaluation, OPNET simulator. ………………………………………………………………………………………………………………………… ÖZ: Gezgin özel amaca yönelik ağlar (MANETs), kablosuz ağlar alanında yeni bir oluşum olup yüzlerce veya binlerce düğümün herhangi bir altyapı veya kontrol merkezi olmaksızın haberleşebilme imkanını sağlamaktadır. Kablosuz düğümlerin (dizüstü bilgisayarlar, kişisel digital yardımcılar ve gezgin telefonlar) özel amaca yönelik senoryolarda hareketleri serbesttir. Buna bağlı olarak, bu tip ağlarda dinamik olarak değişebilen yönlendirme protokollerine gereksinim vardır. Gezgin özel amaca yönelik ağlarda kullanılan yönlendirme protokolleri önceden etkin (proactive), teptin (reactive) ve karma (hybrid) olarak sınıflandırılabilmektedirler. Yönlendirme protokollerinin performanslarını ölçmek ve karşılaştırmak için kullanılan birçok performans ölçü birimleri vardır. Her birinin kendine özgü özellikleri ve iyi olduğu kullanım alanları vardır. Bazı bilinen ölçü birimleri, çıkış is oranı (throughput), seğirme (jitter), paket dağıtım oranı (packet delivery ratio), ortalama sekme sayısı (average number of hops), yön bulma zamanı (route discovery time), ve bir yönden bir yöne gecikmedir (end-to-end delay) Bu tezin bir amacı özel amaca yönelik ağlarda kullanılan ve var olan protokolleri incelemek ve anlamaktır. Diğer bir amacı da OPNET simulatörü kullanarak iyi bilinen OLSR, AODV ve TORA protokollerinin performansını özel amaca yönelik ağlarda orta hızdaki dosya transfer (FTP) protokolünün performansını incelemektedir. OLSR protokolü önceden etkin protokoller sınıfında olup yönlendirme tabloları her sekme üzerinde yapılandırılmaktadır. AODV tepkin protokoller sınıfında olup alıcıya olan rota talep üzerine bulunmantadır. TORA protokolü her iki kategoriye göre çalışabilmektedir. Bu tezde tepkin protokolü olarak kullanılmıştır. Bu çalışmada rastgele ara nokta hareketlilik modeli hareketliliği sağlamak için kullanılmıştır. Performans ölçme birimi olarak, ortalama çıkan iş oranı (average throughput), ortalama ağ yükü (average network load) ve ortalama bir uçtan bir uca gecikme (average end-to end delay) farklı boyutlardaki veri, farklı sekme hızları ve farklı sekme sayıları kullanılarak incelenmiştir. Simulasyon sonuçları seçilen protokollerin farklılıklarını göstermiştir. Protokoller ayni senaryolarda kullanılan ölçü birimlerinde farklı sonuçlar üretmiştir. Genel olarak seçilen ölçü birimlerinde önceden etkin protokoller tepkin protokollerden daha iyi sonuc vermiştir. Simulasyon sonuçlarına göre OLSR protokolü kullanırken sekme sayısını artırdığımız zaman ortalama bir uçtan bir uca gecikme az miktarda yükselmiştir. Buna ek olarak OLSR protokolünde ortalama çıkan iş oranı AODV ve TORA protokollerinden daha fazla çıkmıştır. Dosya boyutu, sekme hızı ve sekme sayısı artırıldığı zaman, etkin protokollerden olan AODV‘nin performsı TORA dan daha iyi çıkmıştır. Ayni zamanda TORA, AODV ve OLSR ile karşılaştırıldığında en yüksek bir uçtan bir uca gecikme ve en düşük çıkan ortalama çıkan iş oranı değerleri vermiştir. Anahtar Kelimeler: Gezgin kablosuz özel amaca yönelik ağlar, simulasyon, yönlendirme protokolleri, performans ölçme / değerlendirme, OPNET simulasyon programı.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2012. Supervisor: Assist. Prof. Dr. Gürcü Öz.
Keywords: Computer Engineering; Mobile communication systems; Ad hoc networks (Computer networks); Mobile Wireless Ad Hoc Networks Simulation Routing Protocols Perofrmance Evaluation OPNET Simulator